2021
DOI: 10.1111/jorc.12361
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural strategies to self‐manage low‐potassium diets in chronic kidney disease

Abstract: Background Dietary potassium restrictions may be challenging to follow, due in part to the restrictive nature of recommendations on foods people enjoy. Little is known how people incorporate low‐potassium diets into their lifestyles. Objective To examine the self‐directed behavioural strategies people employ to follow low‐potassium advice. Design Qualitative methodology. Participants Thirty‐four adults with chronic kidney disease. Approach Semistructured interviews were undertaken in an outpatient department. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Despite an increasing number of self-management interventions tested through research (Donald et al, 2021;Jenkins et al, 2021;M. C. Lee, Wu, et al, 2021;Morris & Lycett, 2021) patients are still experiencing unmet needs in practice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite an increasing number of self-management interventions tested through research (Donald et al, 2021;Jenkins et al, 2021;M. C. Lee, Wu, et al, 2021;Morris & Lycett, 2021) patients are still experiencing unmet needs in practice.…”
Section: Discussionmentioning
confidence: 99%
“…However, this review has identified that people affected by kidney failure receiving HD experienced a lack of support, information, and available resources, with a lack of educational support from their health care providers and shared informed decision‐making. Despite an increasing number of self‐management interventions tested through research (Donald et al, 2021; Jenkins et al, 2021; M. C. Lee, Wu, et al, 2021; Morris & Lycett, 2021) patients are still experiencing unmet needs in practice.…”
Section: Discussionmentioning
confidence: 99%